Analisis Peran Generasi Z dalam Kemenangan Pasangan Calon Dedi Mulyadi dan Erwana Setiawan pada Pilgub Jawa Barat 2024 - Lestari, Aulia Sri Bayu; Heriani, Nur; Munawar, Thalia Kaisah Marsya; Putranto, Algooth (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research aims to analyze the role of Generation Z in the victory of the candidate pair Dedi Mulyadi and Erwan Setiawan in the 2024 West Java Gubernatorial Election. This election holds special significance as West Java is the province with the largest voter base in Indonesia, with a Fixed Voter List (DPT) reaching 31,730,039 people. This study employs a descriptive qualitative method with a literature study approach, analyzing various data sources including official documents and media coverage. The results show that the pair's success is inseparable from their effective digital campaign strategy in reaching Generation Z, with a total social media following of 19.7 million. The pair successfully combined a traditional-cultural approach with modern digital strategies, reflected in their seven comprehensive flagship programs. A Kompas Research and Development survey showed very high support at 65%, far exceeding their closest competitor. This research provides important contributions to understanding the transformation of political campaign strategies in the digital era and the significant role of Generation Z in determining local election outcomes.